Incidence of selected postpartum morbidities and their correlates in Ratnapure - Attygalle, D.E (My University, 2002)
The objective of the study was to assess the incidence of selected postpartum morbidities and to describe factors associated with such morbidity in urban and rural populations in Ratnapura district. Although this problems has been addressed specifically in the national level by introducing iron folate therapy in postpartum mothers, it has not received due attention. The study demonstrated that women could be educated to report important signs and symptoms and much morbidity could be detected and dealt with if regular postpartum visits are instituted. Many of the conditions identified could be managed at field level, while only 9.8 per cent of morbidities needed referral to hospitals. The predictor factors that were indentified in the study could be easily addressed with little change in strategies currently in place in the present MCH system. However the implementation and quality of care would depend on regular supervision and evolution